MICROBIOLOGICAL QUALITY ASSESSMENT OF SUDANESE COASTAL SEA-WATERS WITH SPECIAL REFERENCE TO PORT SUDAN AREA - Omer Abdalla, Ehab; Taha Abdalla Shigidi , Mohammed (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to evaluate faecal pollution in the Sudanese coastal waters near Port Sudan by counting the most important three bacterial indicators of faecal pollution of water which are total coliform, faecal coliform and faecal streptococci using the multiple tube technique to determine the most probable number of indicator bacteria in 100 ml sea water. Fifty sea water samples were collected from 10 stations located along the shore line of the Sudanese coastal waters near Port Sudan as well as the inner waters of both Port Sudan and Suakin and from the open sea water in about five km from Port Sudan. The three indicator bacteria were present in all samples collected from the shore line stations, but none of them was found in the 5 samples collected from the open sea. High counts were observed in the samples collected from the inner waters of Port Sudan in both Khour Salalab and Khour Kilab which receive annually considerable amounts of fresh water from the run–off from the land. The counts decreased when samples were collected away from Port Sudan either to the south or north. The study showed low counts of indicator bacteria in Suakin inner waters than those of Port Sudan and the highest counts of the indicators observed in this study were 180, 180 and 350 bacteria per 100 ml sea water for total coliform, faecal coliform and faecal streptococci, respectively. In coastal waters it is difficult to determine the exact source of pollution as many sources combine together, but in this case probably the run-off from land might be the main source due to the high counts in the inner waters which receive the run-off from land.